A numerical method for solving inverse forming problems in the creep mode - Bormotin, K.S. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2014)
The inverse quasi-static problems of the creep theory is formulated in the form of optimum control. A number of optimum laws of deformation in creep are proposed on the basis of the minimization damage criterion in the functionals of inverse problems. When solving inverse forming problems by an iterative method, a continuous optimum loading function dependent on two parameters is used. A method for finding the parameters according to the given initial conditions is also proposed and implemented numerically. At each step of the iterative method, the solving procedure is based on a finite element method in the framework of the MSC.Marc software system. A comparative analysis of numerical results is given in the case of plate bending for various modes of loading.